Analisis Faktor-Faktor yang Mempengaruhi Perilaku Konsumtif Mahasiswa Pengguna Marketplace Shopee di Era Digital (Studi Kasus pada Mahasiswa Prodi Ekonomi Universitas Bhineka PGRI Tulungagung) - Puspitasari, Devi Lia; Umami, Nailariza (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This research is motivated by changes in student consumption patterns in the digital era, especially through the use of the Shopee marketplace. Features such as discounts, free shipping, Shopee PayLater, and promotions based on algorithms and social media make shopping activities easier and more attractive. However, this convenience also encourages the emergence of consumptive behavior. This phenomenon shows the importance of studying internal and external factors that influence student consumptive behavior, especially in academic environments such as the Economics Education Study Program, Bhineka PGRI University, Tulungagung. Problem formulation: (1) What are the internal factors that influence the consumptive behavior of students who use the Shopee marketplace at Bhineka PGRI University, Tulungagung?; (2) What are the external factors that influence the consumptive behavior of students who use the Shopee marketplace at Bhineka PGRI University, Tulungagung?; (3) To what extent do internal and external factors influence the consumptive behavior of students who use Shopee at Bhineka PGRI University, Tulungagung? The method used is qualitative with a case study approach to students of the Economics Education Study Program at Bhineka PGRI Tulungagung University who actively use Shopee. The data collection technique was carried out by in-depth interviews with seven informants selected purposively based on certain criteria. The results of this study indicate that: (1) Internal factors that influence the consumer behavior of students who use Shopee at Bhineka PGRI Tulungagung University consist of personal motivation, emotions, self-control in shopping, impulsive buying and following trends that encourage intensive online shopping, especially in the fashion category and other lifestyle needs (2) External factors that influence the consumer behavior of students who use Shopee include promotions, discounts, flash sales, the influence of social media and influencers, social environment and peers, ease of access and features of the Shopee application (3) Internal and external factors on the consumer behavior of Shopee students at Bhineka PGRI Tulungagung University are interrelated and reinforce each other, where internal psychological needs are triggered by external stimuli such as promotions and social pressure, thus forming intense consumer habits that are potentially financially risky, so that financial literacy is important to control this behavior.